Effect of electric stimulation on human chondrocytes and mesenchymal stem cells under normoxia and hypoxia - Hiemer, Bettina (Mol Med Rep, 2018)
During joint movement and mechanical loading, electric potentials occur within cartilage tissue guiding cell development and regeneration. Exposure of cartilage exogenous electric stimulation (ES) may imitate these endogenous electric fields and promote healing processes. Therefore, the present study investigated the influence of electric fields on human chondrocytes, mesenchymal stem cells and the co-culture of the two. Human chondrocytes isolated from articular cartilage obtained post-mortally and human mesenchymal stem cells derived from bone marrow (BM-MSCs) were seeded onto a collagen-based scaffold separately or as co-culture. Following incubation with the growth factors over 3 days, ES was performed using titanium electrodes applying an alternating electric field (700 mV, 1 kHz). Cells were exposed to an electric field over 7 days under either hypoxic or normoxic culture conditions. Following this, metabolic activity was investigated and synthesis rates of extracellular matrix proteins were analyzed. ES did not influence metabolic activity of chondrocytes or BM-MSCs. Gene expression analyses demonstrated that ES increased the expression of collagen type II mRNA and aggrecan mRNA in human chondrocytes under hypoxic culture conditions. Likewise, collagen type II synthesis was significantly increased following exposure to electric fields under hypoxia. BM-MSCs and the co-culture of chondrocytes and BM-MSCs revealed a similar though weaker response regarding the expression of cartilage matrix proteins. The electrode setup may be a valuable tool to investigate the influence of ES on human chondrocytes and BM-MSCs contributing to fundamental knowledge including future applications of ES in cartilage repair.